2006
DOI: 10.1210/jc.2006-0844
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Insulin-Like Growth Factor-I, Insulin Sensitivity, and Secretion from Birth to Age Three Years in Small-for-Gestational-Age Children

Abstract: IGF-I levels increased rapidly from birth in SGA, but not AGA children. During the key first-year growth period, IGF-I levels were related to beta-cell function and longitudinal growth. In contrast, by 3 yr, when catch-up growth was completed, IGF-I levels were related to body mass index and IR, and these higher IGF-I levels in SGA infants might indicate the presence of relative IGF-I resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 32 publications
4
54
1
2
Order By: Relevance
“…In that study, a link was suggested between IUGR and polycystic ovary syndrome (PCOS), possibly caused by intrauterine programming affecting reproduction function in low-BW infant girls. Another explanation could be the positive relationship between insulin and AMH, as high-BW infants as well as low-BW infants who show catch-up growth are likely to have high insulin levels (33,34). Other recent studies showed no relation of BW with PCOS and AMH levels (30,35).…”
Section: Discussionmentioning
confidence: 98%
“…In that study, a link was suggested between IUGR and polycystic ovary syndrome (PCOS), possibly caused by intrauterine programming affecting reproduction function in low-BW infant girls. Another explanation could be the positive relationship between insulin and AMH, as high-BW infants as well as low-BW infants who show catch-up growth are likely to have high insulin levels (33,34). Other recent studies showed no relation of BW with PCOS and AMH levels (30,35).…”
Section: Discussionmentioning
confidence: 98%
“…Serum IGF-I levels were determined by radioimmunoassay [22] . The sensitivity of this assay is 5.0 ng/ml, intra-assay CV is 8.6%, and the inter-assay CV is 10.2%.…”
Section: Methodsmentioning
confidence: 99%
“…Serum insulinlike growth factor 1 (IGF-1) was measured by radioimmunoassay by using a commercial kit (LincoResearch Inc, St Charles, MO) (sensitivity 5 ng/mL: intra-and interassay coefficients of variation: 8.6% and 10.2%, respectively). 17 In each of the visits, skeletal-maturation was assessed in duplicate by using an ultrasound-transmission method (BonAge; Sunlight Co, Medical, TelAviv, Israel). 18 …”
Section: Physical/sexual Maturationmentioning
confidence: 99%